2014
DOI: 10.1007/s00404-014-3258-9
|View full text |Cite
|
Sign up to set email alerts
|

Does endometrial injury improve implantation of frozen–thawed embryos?

Abstract: Based on the results of this pilot study, EI in the luteal phase of the cycle preceding the frozen embryo transfer cycle does not appear to significantly improve implantation or clinical pregnancy rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 13 publications
2
19
0
Order By: Relevance
“…Elsewhere, El‐Khayat et al evaluated the effect of ESI on office hysteroscopy in the cycle preceding IUI, and observed no evidence of significant improvement in the clinical pregnancy rate in comparison with the control group . In a similar way, Baum et al and Dunne and Taylor found no difference in pregnancy outcome between the study groups (ESI vs control) in the IVF and frozen embryo cycles, respectively …”
Section: Discussionmentioning
confidence: 99%
“…Elsewhere, El‐Khayat et al evaluated the effect of ESI on office hysteroscopy in the cycle preceding IUI, and observed no evidence of significant improvement in the clinical pregnancy rate in comparison with the control group . In a similar way, Baum et al and Dunne and Taylor found no difference in pregnancy outcome between the study groups (ESI vs control) in the IVF and frozen embryo cycles, respectively …”
Section: Discussionmentioning
confidence: 99%
“…It has been known that EI can remove irregular hyperplasia of endometrial tissue, promote epithelial cells, stromal cells proliferation and differentiation, and enrich the endometrial blood flow . Up to now, there were six trials focusing on the effect of EI in luteal phase prior to frozen–thawed ET cycle . The results of these trials seem contradictive to each other and no firm conclusion can be made whether performing EI in luteal phase of the subsequent frozen–thawed ET cycle is beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…8 Up to now, there were six trials focusing on the effect of EI in luteal phase prior to frozen-thawed ET cycle. [17][18][19][28][29][30] The results of these trials seem contradictive to each other and no firm conclusion can be made whether performing EI in luteal phase of the subsequent frozenthawed ET cycle is beneficial. Among the studies, only one study focused on the effect of EI in luteal phase before a frozen-thawed ET cycle on live birth rate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations